Multiple cleaner species provide simultaneous services to coral reef fish clients. (23rd December 2020) - Rose, Amelia; Titus, Benjamin M.; Romain, Joseph; Vondriska, Clayton; Exton, Dan A.
Abstract : Cleaning symbioses on tropical coral reefs are typically documented between two species: a single client fish and one or more conspecific cleaners. However, multiple cleaner species living sympatrically in the Caribbean have been anecdotally reported to simultaneously clean the same client. Nothing is known about the patterns and processes driving these interactions, which may differ from those involving a single cleaner species. Here, we used remote underwater videography on three reefs in Honduras to record simultaneous cleaning interactions involving Pederson's cleaner shrimp ( Ancylomenes pedersoni ) and cleaner gobies ( Elacatinus spp.). A pilot study on adjacent shrimp and goby stations found interactions were always initiated by shrimp. A larger, multi-year dataset shows cleaner gobies joined 28% of all interactions initiated at A. pedersoni cleaning stations with cleaner gobies residing nearby. Client body size significantly predicted simultaneous cleaning interactions, with 45% of interactions simultaneous for clients greater than 20 cm total body length compared with only 8% for clients less than 20 cm. We also found that simultaneous cleaning interactions lasted over twice as long as shrimp-only interactions. We propose these novel multi-species interactions to be an ideal model system to explore broader questions about coexistence, niche overlap and functional redundancy among sympatric cleaner species.